(untitled) (Journal of Asian Development Studies, 2025)
This study examines the relationship between foreign reserves, financial development, and institutional qualityin BRICS countries. Based on a country’s Foreign Reserves, like gold reserves, foreign currencies, Special Drawing Rights (SDRs), and foreign reserves in the IMF,its influence on a country’s financial developments and institutions. In addition, trade openness, quality of natural resources (such as renewable energy), and GDP were taken as control variables. The result reveals that when a country’s economy is sound, its Foreign Reserves influence its overall financial development positively and enhance its institutions. In a country facing an economic crisis, foreign reserves are less influential, failing to exert a positive, sustained influence on financial developments and institutions. Financial developments strengthen a country’s financial system, boosting its economy and reducing poverty. Sound institutions lay a foundation for a country’s stability and risk management. The study shows that Foreign Reserves play a significant role in holding back a country’s financial development in BRICS states. Furthermore, its influence is stronger when Institutional Quality is high